Objective and Existential Lecturer Authenticity as Drivers of Student Engagement and Learning Performance in Tourism and Hospitality Programmes - Hijriantomi Suyuthie; Rian Surenda; Rahmi Fadilah; Siti Fatma (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines how lecturers’ authenticity—operationalised through objective authenticity (a lecturer’s adherence to transparent course standards and consistent professional conduct) and existential authenticity (the warmth, sincerity, and meaningfulness students perceive in the learning experience)—shapes student engagement and perceived learning performance in tourism and hospitality programmes. Drawing on Self-Determination Theory, a quantitative survey was administered to 196 undergraduate students across West Sumatra, Indonesia (August–October 2025), and the proposed model was tested via partial least squares structural equation modelling (PLS-SEM) using a two-stage higher-order construct approach. Results indicate that existential authenticity exerted a stronger positive effect on student engagement (β = 0.34, p < 0.001) than objective authenticity (β = 0.17, p = 0.048). St udent engagement predicted perceived learning performance (β = 0.39, p < 0.001). The model explained 26% of variance in engagement (R² = 0.26) and 15% in perceived learning performance (R² = 0.15). Student engagement fully mediated the relationship between objective authenticity and perceived learning performance, and partially mediated the relationship between existential authenticity and perceived learning performance. Findings underscore the value of meaning-centred, sincere teaching practices for building durable student engagement and enhancing perceived learning outcomes in practice-oriented hospitality programmes.